Welfare state regimes, infant mortality and life expectancy: integrating evidence from East Asia. Issue 7 (31st August 2011) - Chuang, Ying-Chih; Chuang, Kun-Yang; Chen, You-Rong; Shi, Bo-Wen; Yang, Tzu-Hsuan
Abstract : Background: This longitudinal study builds on the cross-sectional work of Karim et al and examines the influence of welfare state regime on population health with a particular focus on East Asian welfare states (eg, Hong Kong, Japan, Korea, Singapore and Taiwan). Methods: Data were extracted from the Organisation of Economic Co-operation and Development Data Set, World Development Indicators and Asian Development Bank's key indicators from 1980 to 2006. Infant mortalities and life expectancy were used as health-outcome varables. Thirty-one countries were categorised into six types of welfare regimes: Scandinavian, Anglo-Saxon, Bismarckian, Southern, Eastern European and East Asian. Mixed models were applied to analyse the data with repeated measurements. Results: In keeping with Karim et al, Scandinavian and Eastern European welfare states have lower and higher infant mortalities respectively compared with East Asian welfare states. Eastern European welfare states had a lower life expectancy than East Asian welfare states. Most welfare states had a higher social, health and education expenditure, and higher densities of physicians than East Asian welfare states. Conclusion: East Asian welfare states did not have worse health than most welfare states. Future studies should continue to incorporate East Asian countries in the typology of welfare regimes that include more social, economic, political and healthcare system characteristic variables to provide insight on the mechanism by which welfare-state regimes influence population health.